Controlling the growth of zirconia needles precursor from a liquid crystal template - Freitas, F. G. [UNESP]; Sarmento, V. H. V. [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier B.V., 2010)
This work reports the directional growth of macroscopic ceramic needles by combining a thermo-responsive Sulfated hydroxy zirconyl (SHZ) hydrosol with a swollen hexagonal liquid crystal (SHLC). The effect of the molar ratio R(s) = [Zr(4+)]/[SO(4)(2-)] on the thermo-stability of both the SHZ hydrosol and the SHLC. and also on the nucleation and 1 D-growth of ceramic particles was investigated. The dynamics of the thermo-induced aggregation growth process was monitored in situ by rheological property measurements. The results show that by increasing the R, the kinetic stability of the system in the sol state increases, leading to the formation of a less branched framework during the thermo-induced aggregation process. Furthermore, the small-angle X-ray diffraction (XRD) results show that the thermo-stability of the SHLC employed as soft template is improved by increasing the R, Both effects allow us to induce the particle's nucleation by heating the SHLC template to a moderate temperature (approximate to 50 degrees C), while the kinetics of the needle's growth is enhanced by increasing the [Zr(4+)]/[SO(4)(2-)] molar ratio. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Sol-gel processes; Liquid crystal template; Zirconia needles precursor